Adolescents and parental perception of family strength: relation to Malay adolescent emotional and behavioural adjustments - Arshat, Zarinah (Center for Promoting Ideas, 2013)
Adolescent and parental evaluation of family strength may have different significant impact on adolescent emotional and behavioural adjustment. The aim of this study was to examine adolescents’ and parents’ perception of family strength and the relationship of these perceptions to adolescent adjustment. 180 families participated in the study through a survey and standardized self-administered questionnaires were utilised. Significant differences were found regarding family strength between adolescent and their parent. Result showed adolescent perception of family strength was a significant predictor of their emotional and behavioural adjustment. The results of this study emphasise the importance of adolescent perception of family strength, and provide support to be taken into account when implementing any family programme.